2021
DOI: 10.1371/journal.pone.0244949
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 and interferon-γ single nucleotide polymorphisms in Egyptian patients with tuberculosis

Abstract: Background Interleukin-18 (IL-18) and interferon-γ (IFN-γ) are cytokines of crucial role in inflammation and immune reactions. There is a growing evidence supporting important roles for IL-18 and IFN γ in tuberculosis (TB) infection and anti-tuberculosis immunity. Objective To evaluate the role of polymorphisms in IL-18-607 and -137 and INF-γ +874 in susceptibility to TB infection among Egyptian patients. Methods A case control study was conducted to investigate the polymorphism at IL-18-607, -137 and INF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Although studies correlating haplotypes of IFNG gene and cytokine levels and/or susceptibility to infectious disease have not yet been carried out in dog, several studies described different haplotypes in this gene as being related to the susceptibility or resistance to infectious diseases in humans, including parasitic infection diseases. For example, some authors associated IFNG haplotypes with the susceptibility to virus infection, such as hepatitis B virus [59], T-lymphotropic virus type 1 infection [60], or tuberculosis [61,62], as well as bacterial infections such as brucellosis [63], or parasitic infections such as malaria [64,65]. Related to leishmaniasis, Kalani et al [66] found several haplotypes in the IFNG gene related to susceptibility and resistance to visceral leishmaniasis in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies correlating haplotypes of IFNG gene and cytokine levels and/or susceptibility to infectious disease have not yet been carried out in dog, several studies described different haplotypes in this gene as being related to the susceptibility or resistance to infectious diseases in humans, including parasitic infection diseases. For example, some authors associated IFNG haplotypes with the susceptibility to virus infection, such as hepatitis B virus [59], T-lymphotropic virus type 1 infection [60], or tuberculosis [61,62], as well as bacterial infections such as brucellosis [63], or parasitic infections such as malaria [64,65]. Related to leishmaniasis, Kalani et al [66] found several haplotypes in the IFNG gene related to susceptibility and resistance to visceral leishmaniasis in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies correlating haplotypes of IFNG gene and cytokines levels and/or susceptibility to infectious disease have not yet been carried out in dog, several studies described different haplotypes in this gene to be related to the susceptibility or resistance to infectious diseases in humans, including parasitic infection diseases. For example, some authors related IFNG haplotypes with the susceptibility against virus infection as hepatitis B virus [60], T-lymphotropic virus type 1 infection [61], or tuberculosis [62,63], against bacterial infection as brucellosis [64], and against parasitic infection as malaria [65,66]. Related to leishmaniasis, Kalani et al (2019) found several haplotypes in IFNG gene related to susceptibility and resistance to visceral leishmaniasis in Iran [67].…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 gene is located on chromosome 11q22.2–q22.3 and contains numerous SNPs in the promoter region [ 114 , 115 ]. It encodes proinflammatory cytokine interleukin-18 (IL-18), which is central to the inflammatory chain reaction.…”
Section: Genes and Snps That May Be Associated With Ir And Atheroscle...mentioning
confidence: 99%